tìm n ϵ Z biết
(2n+1)⋮(n-5)
(n2+3)⋮(n-1)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{2.2306}{1+\dfrac{1}{1+2}+\dfrac{1}{1+2+3}+\dfrac{1}{1+2+3+4}+...+\dfrac{1}{1+2+...+2306}}\)
Ta có: f(0) = 1 => f(0) = d = 1
f(-1) = 2 => f(-1) = -a + b - c + d = 2 => -a + b - c = 1
=> a = b - c - 1 (1)
f(1/2) = 3 => f(1/2) = 1/8a+ 1/4b + 1/2c + d = 3
=> 1/8a + 1/4b + 1/2c = 2 =>a + 2b + 4c = 16 (2)
f(1) = 7 => f(1) = a + b + c + d = 7 => a + b + c = 6 (3)
Thay (1) vào (2) và (3)
(2) b - c + 1 + 2b + 4c = 16 => 3b + 3c = 15 => b + c = 5
(3) b - c + 1 + b + c = 6 -> 2b = 5 => b = 5/2
=> c = 5 - 5/2 = 5/2
=> a = b - c + 1 = 5/2 - 5/2 + 1 = 1
+, Vì f (0) = 1 => d = 1
ta được: a. 03 + b. 02 + c .0 + 1 = 1
+, Vì f ( -1) = 2 => = -a + b - c + 1 = 2 => -a + b - c = 2-1 = 1
=> a = b - c - 1 (1)
+, Vì f (1/2) = 3 => f(1/2) = 1/8a+ 1/4b + 1/2c + d = 3
=> 1/8a + 1/4b + 1/2c = 2 =>a + 2b + 4c = 16 (2)
f(1) = 7 => f(1) = a + b + c + 1 = 7 => a + b + c = 7-1 = 6 (3)
Thay (1) vào (2) và (3)
=> b - c + 1 + 2b + 4c = 16 => 3b + 3c = 15 => b + c = 5
=> b - c + 1 + b + c = 6 => 2b = 5 => b = 5/2
=> c = 5 - 5/2 = 5/2
=> a = b - c + 1 = 5/2 - 5/2 + 1 = 1
c. -3/4 < A/10 < -3/5
<=> -15/20 < 2A/20 < -12/20
<=> -15 < 2A < -12
<=> -15/2 < A < -6
<=> -7,5 <A < -6
Vì A là số nguyên nên A = -7
c. -3/4 < A/10 < -3/5
<=> -15/20 < 2A/20 < -12/20
<=> -15 < 2A < -12
<=> -15/2 < A < -6
<=> -7,5 <A < -6
Vì A là số nguyên nên A = -7
-11/21 <0<13/30 vậy -11/21 < 13/30
35/85 = 7/17 <7/15<8/15 vậy 35/85 < 85/93
61/60 > 1 > 85/93 vậy 61/60 > 85/93
11/17 = 110/170 = 1- 60/170 < 1 - 60/173 = 163/173
-11/21 <0<13/30 vậy -11/21 < 13/30
35/85 = 7/17 <7/15<8/15 vậy 35/85 < 85/93
61/60 > 1 > 85/93 vậy 61/60 > 85/93
11/17 = 110/170 = 1- 60/170 < 1 - 60/173 = 163/173
a) \(2n+1=2\left(n-5\right)+11\)
Để \(\left(2n+1\right)⋮\left(n-5\right)\Rightarrow11⋮\left(n-5\right)\)
\(\Rightarrow\left(n-5\right)\inƯ\left(11\right)=\left\{1;-1;11;-11\right\}\Rightarrow n\in\left\{6;4;16;-6\right\}\)
b) \(n^2+3=n\left(n-1\right)+\left(n-1\right)+4=\left(n-1\right)\left(n+1\right)+4\)
Để \(\left(n^2+3\right)⋮\left(n-1\right)\Rightarrow4⋮\left(n-1\right)\)
\(\Rightarrow\left(n-1\right)\inƯ\left(4\right)=\left\{1;-1;2;-2;4;-4\right\}\)
\(\Rightarrow n\in\left\{2;0;3;-1;5;-3\right\}\)